Pattern of peer review proforma of medical journals of Pakistan - Shah, Faaiz Ali (Pak J Med Sci, 2019)
OBJECTIVE: To analyze the contents and format of peer review proforma of Medical journals of Pakistan. METHODS: This descriptive study was conducted in the Department of Orthopaedics and Traumatology Lady reading Hospital Peshawar Pakistan from 3(rd) August 2018 to 9(th) February 2019.An email was sent to the chief editors of all the medical journals listed on the official website (www.pmdc.org.pk) of Pakistan Medical and Dental Council (PM&DC).They were requested to send peer review proformas of their journals. The received proformas were analyzed for major contents and format or style. The proforma had a structured format when each portion of the manuscript i.e, title, abstract, key words, methodology, results, discussion, conclusion and references were individually sectioned for evaluation. Whereas in the unstructured proformas the reviewer was asked to assess the manuscript as a whole. RESULTS: We received 41 proformas via emails. Majority (82.9%) of the proformas were structured while 17% were unstructured. A scoring or rating system for the manuscript was present in 31.7% of the proformas while 43.9% of the proformas were without any scoring system. Guidelines for the peer reviewers were given in 58.5% of the proformas. The peer review policy (closed or open) was mentioned in only 7.3%.About 9.7% of the proformas asked the reviewers to disclose conflict of interests. CONCLUSION: A spectrum of contents and format of peer review proformas of medical journals were observed. We found structured peer review proforma with a scoring scale comprehensive and more appropriate for peer review.